Bioprospecting autochthonous marine microalgae strain from the Arabian Gulf Seawater, Kuwait for biofuel feedstocks - Al-Hamar, Bader (2022)
Bioprospecting programs are the key to increasing the current portfolio of indigenous microalgal strains accessible for different applications in microalgal biotechnology. In this work, nine fast-growing microalgal strains isolated from Kuwait's Arabian/Persian Gulf coastal waters were evaluated for their potential as biofuel feedstocks. 18S rRNA gene sequencing showed that the strains belong to five different genera: Chlorella, Nannochloris, Scenedesmus, Tetraselmis, and Nannochloropsis. In terms of the total lipid content, in comparison to the other strains, Tetraselmis sp. KUBS13G and Tetraselmis sp. KUBS16G displayed higher lipid contents of 29.56% dry weight (DW) and 26.13% DW, respectively, dominated by palmitic and oleic acids. Fuel properties calculated from the fatty acid methyl esters (FAMES) by empirical equations were compared with EN14214 (European) and ASTM D6751--02 (American) biodiesel standards. Multicriteria decision analysis (MCDA) methods, such as the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) and Graphical Analysis for Interactive Assistance (GALA), were used to select suitable microalgae for biofuel feedstock based on their biodiesel fuel properties. Overall, the results suggested that the indigenous microalgal strain Tetraselmis, particularly Tetraselmis sp. KUBS37G, and Scenedesmus sp. KUB Sl7R are the most suitable strains for biofuel feedstock owing to their improved fuel properties, such as density (rho) (0.88 g cm-3), low kinematic viscosity (3.1 mm2 s-1), high cetane number (54 and 56, respectively), high oxidation stability (14.6 hr and 14.8 hr), and cold filter plugging point (1.0 degrees C and -6.1 degrees C).